2014
DOI: 10.1167/iovs.14-15072
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Peripapillary Retinal Nerve Fiber Layer and Inner Retinal Thickness Among Two Spectral Domain Optical Coherence Tomography Devices

Abstract: Measurement of pRNFL and macular RNFL-GCL-IPL thickness has a high degree of repeatability for both OCT devices. Despite a high correlation between measurements of the two OCT devices and fair to excellent ICC values representing a high consistency in the measurements of the two devices, RTVue measured a thicker macular RNFL-GCL-IPL and pRNFL thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…Our study made it also possible to evaluate the SLO based image alignment function of the RS-3000 OCT. Though the repeatability figures for the various TR thickness parameters were highly satisfactory, the corresponding figures for cpRNFL thickness were relatively low, even when compared to published results obtained with other OCT systems [ 23 , 25 , 29 ]. Since the same images were used to calculate the CV and ICC values for all parameters including those which were highly reproducible, we think that the image alignment function used by us is clinically useful, and cannot be considered as the reason of the lower repeatability of the cpRNFL thickness parameters compared to cpTR thickness.…”
Section: Discussionmentioning
confidence: 54%
“…Our study made it also possible to evaluate the SLO based image alignment function of the RS-3000 OCT. Though the repeatability figures for the various TR thickness parameters were highly satisfactory, the corresponding figures for cpRNFL thickness were relatively low, even when compared to published results obtained with other OCT systems [ 23 , 25 , 29 ]. Since the same images were used to calculate the CV and ICC values for all parameters including those which were highly reproducible, we think that the image alignment function used by us is clinically useful, and cannot be considered as the reason of the lower repeatability of the cpRNFL thickness parameters compared to cpTR thickness.…”
Section: Discussionmentioning
confidence: 54%
“…The use of optical coherence tomography (OCT) to examine the retinal nerve fiber layer (RNFL) has become essential in daily clinical practice. Several studies have shown the OCT clinical usefulness to study many retinal and optic nerve diseases [1,2], along with its excellent reproducibility [3].…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available OCT systems are able to capture high-resolution, three-dimensional (3D) volumes of the retina and its sublayers 15,16. The propriety software automatically measures the thickness of pRNFL15,16 and GCIPL in sectors defined by the Early Treatment Diabetic Retinopathy Study (ETDRS) 15,17. The diagnostic value of these core measurements is well documented;16 yet, other intraretinal layers provided additional and complimentary information regarding the health of the retina 18.…”
Section: Introductionmentioning
confidence: 99%